Adapting business model with Covid-19 pandemic using business strategic cards - Juniarti, Rosa Prafitri; Ridlwan, Ahmad Ajib; Arifah, Ika Diyah Candra; Fatoni, Fandi; Fahrullah, A'rasy; Kautsar, Achmad (Technium Social Sciences Journal, 2021)
The Covid-19 pandemic crisis has dealt a severe blow to the Indonesian economy, especially the informal sector that driven by small and medium enterprises (SMEs). The implementation of physical and social distancing as part of a health protocol to overcome the pandemic forces food and beverage SMEs to adjust its product quality and service provision based on these standards and become more consumer-oriented. It is relevant to changing consumer lifestyles, which prioritize hygiene and product benefits for health. To adapt to this situation, SMEs are also required to adjust business models that support work flexibility, collaborative teamwork, and organize workplaces with incremental and iterative work sequences to achieve constant developing changes and help them to achieve their goals more effectively. Therefore, this study aims to analyze the process of adaptation of business models in food and beverage SMEs in Surabaya to the Covid-19 pandemic crisis.